The body in the marching bands. : 1st International Seminar (The Voz a Vos Bulletin, 2021)
It is about the marching bands in the 1st International Seminar: The body in marching bands organized by the World Association of Marching Show Bands WAMSB in agreement with the Antonio Nariño University and under the coordination of the Bachelor of Performing Arts from the Faculty of Education.
Keywords: Music; Body; Marching bands